2013
DOI: 10.1038/clpt.2013.80
|View full text |Cite
|
Sign up to set email alerts
|

Replication of TPMT and ABCC3 Genetic Variants Highly Associated With Cisplatin-Induced Hearing Loss in Children

Abstract: Cisplatin is a widely used chemotherapeutic agent for the treatment of solid tumors. A serious complication of cisplatin treatment is permanent hearing loss. The aim of this study was to replicate previous genetic findings in an independent cohort of 155 pediatric patients. Associations were replicated for genetic variants in TPMT (rs12201199, P = 0.0013, odds ratio (OR) 6.1) and ABCC3 (rs1051640, P = 0.036, OR 1.8). A predictive model combining variants in TPMT, ABCC3, and COMT with clinical variables (patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 47 publications
4
125
3
3
Order By: Relevance
“…Variants in COMT (rs9332377 and rs4646316) have shown similar trends of associations in four independent pediatric cohorts (Table S1) 15,23,26 . These associations reached statistical significance only in two of the four cohorts while two additional studies have also reported effect sizes in the opposite direction 25,27 .…”
Section: Methlytransferase Genes (Tpmt and Comt)mentioning
confidence: 76%
See 4 more Smart Citations
“…Variants in COMT (rs9332377 and rs4646316) have shown similar trends of associations in four independent pediatric cohorts (Table S1) 15,23,26 . These associations reached statistical significance only in two of the four cohorts while two additional studies have also reported effect sizes in the opposite direction 25,27 .…”
Section: Methlytransferase Genes (Tpmt and Comt)mentioning
confidence: 76%
“…Rednam et al reported an opposite effect of GSTP1 rs1965 on cisplatin-induced hearing loss in a pediatric medulloblastoma cohort 42 . Furthermore, five studies (4 pediatric, 1 adult) reported no significant association of GSTP1 with hearing loss 15,23,35,37,38 . Overall, evidence regarding an effect of GSTP1 rs1695 on ototoxicity is thus inconsistent (Table S4) (+ evidence).…”
Section: Gluthathione S-transferases (Gsts)mentioning
confidence: 99%
See 3 more Smart Citations